2009
DOI: 10.1371/journal.pone.0006144
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Ethylene Biosynthesis Enzyme Leads to Andromonoecy in Two Cucumis Species

Abstract: Andromonoecy is a widespread sexual system in angiosperms, characterized by plants carrying both male and bisexual flowers. Monoecy is characterized by the presence of both male and female flowers on the same plant. In cucumber, these sexual forms are controlled by the identity of the alleles at the M locus. In melon, we recently showed that the transition from monoecy to andromonoecy result from a mutation in 1-aminocyclopropane-1-carboxylic acid synthase (ACS) gene, CmACS-7. To isolate the andromonoecy gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
132
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 39 publications
(53 reference statements)
1
132
0
2
Order By: Relevance
“…Recently, Boualem et al (2008) and Li et al (2009) reported that mutation of a melon and cucumber ACS isogene (CmACS-7 and CsACS2, respectively) resulted in the transition from monoecy to andromonoecy. Thus, CmACS-7 (Boualem et al, 2008) and CsACS2 (Boualem et al, 2009;Li et al, 2009) repress stamen development in female flowers. CmACS-7 and CsACS2 are also members of the type 3 ACS isozyme subfamily.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Boualem et al (2008) and Li et al (2009) reported that mutation of a melon and cucumber ACS isogene (CmACS-7 and CsACS2, respectively) resulted in the transition from monoecy to andromonoecy. Thus, CmACS-7 (Boualem et al, 2008) and CsACS2 (Boualem et al, 2009;Li et al, 2009) repress stamen development in female flowers. CmACS-7 and CsACS2 are also members of the type 3 ACS isozyme subfamily.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, application of ethylene to monoecious cucumber plants promotes the formation of female flowers (MacMurray and Miller, 1968;was first isolated by Kamachi et al (1997), who demonstrated that the expression of the CS-ACS2 gene coincides with development of female flowers in monoecious and gynoecious cucumber plants. Recently, the CS-ACS2 gene was identified as the M gene (Boualem et al, 2009;Li et al, 2009). Thus, both F and M genes encode ACC synthase and ethylene is considered a sex hormone in cucumber plants.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, stamen development is regulated by ethylene derived from the CS-ACS2 gene in cucumber plants ( Fig. 1A; Boualem et al, 2009;Li et al, 2009). Because the amino acid sequences of CmACS-7 and CS-ACS2 show a high degree of similarity (98%) (Boualem et al, 2008(Boualem et al, , 2009Li et al, 2009), these genes are homologs in Cucumis plants.…”
Section: Discussionmentioning
confidence: 95%
“…1A; Boualem et al, 2009;Li et al, 2009). Because the amino acid sequences of CmACS-7 and CS-ACS2 show a high degree of similarity (98%) (Boualem et al, 2008(Boualem et al, , 2009Li et al, 2009), these genes are homologs in Cucumis plants. This suggests that the mechanism of not only sex expression regulated by ethylene but also the induction of functional bisexual flowers by ethylene inhibitors in gynoecious plants is similar in cucumber and melon plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation